2014
DOI: 10.1177/1474474014560998
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous identity and environmental governance in Guyana, South America

Abstract: In an era of increasing access to digital technologies, Indigenous communities are progressively more able to present sophisticated and differentiated narratives in order to maximise their long-term survival. In this paper, we explore how Indigenous communities use participatory video and participatory photography as tools of Indigenous media to enhance, adapt, and/or reinforce their collective social memory.This social memory is key for identity formation and self-representation, and the ways in which Indigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 44 publications
0
23
0
1
Order By: Relevance
“…Esas representaciones pueden apreciarse en algunos casos en actividades tradicionales cotidianas (e.g. agricultura, artesanía, arte textil, medicina tradicional, alimentos típicos, fiestas, danzas, rituales y tradición oral) elementos que conforman el patrimonio cultural en las comunidades indígenas (Mistry et al, 2015). Patrimonio que se integra al desarrollo de tecnologías y conocimientos fundamentales para la obtención de la base alimenticia, fue además, punto de partida de las civilizaciones con agricultura intensiva de altos rendimientos y poca mano de obra pese a no contar con herramientas de metal, la rueda, la tracción animal o arado (Bonfil 1987;Hernández, 1988).…”
Section: Introductionunclassified
“…Esas representaciones pueden apreciarse en algunos casos en actividades tradicionales cotidianas (e.g. agricultura, artesanía, arte textil, medicina tradicional, alimentos típicos, fiestas, danzas, rituales y tradición oral) elementos que conforman el patrimonio cultural en las comunidades indígenas (Mistry et al, 2015). Patrimonio que se integra al desarrollo de tecnologías y conocimientos fundamentales para la obtención de la base alimenticia, fue además, punto de partida de las civilizaciones con agricultura intensiva de altos rendimientos y poca mano de obra pese a no contar con herramientas de metal, la rueda, la tracción animal o arado (Bonfil 1987;Hernández, 1988).…”
Section: Introductionunclassified
“…The identification of strategies under each system viability category between the three communities is analysed and discussed in Berardi et al (2013b) and Mistry et al (2015a). We found that there were similarities between the communities in terms of existence strategies (all three communities felt that access to land and waterways was a fundamental prerequisite for their continued existence), ideal performance (all three communities had practices that promoted the efficient use of titled land), flexibility strategies (all three communities aspired to the development of more options for food and health security), resistance strategies (all three communities had practices that kept traditions alive and protected the environment), adaptability strategies (all three communities used nonindigenous technologies in ways that significantly improved their well-being), and coexistence strategies (all three communities sought effective partnerships at regional, national, and international levels).…”
Section: Resultsmentioning
confidence: 99%
“…Through in-depth discussions, the representations of viability strategies and their relationships were validated and refined where necessary, and then presented back to the three villages in the form of revised spray diagrams for final agreement and comments. A detailed analysis of the visual representations in the PP and PV are provided in Mistry et al (2015a).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, indigenous community researchers carried out and led all field-related activities, including community engagement, PV and PP recordings, and sharing. Reporting and reflection on all these approaches are presented elsewhere (see Berardi et al 2013b, 2015a. We present results only from Stage 4, the final phase of the project involving CP2PKE between communities.…”
Section: Introductionmentioning
confidence: 99%